2016
DOI: 10.1530/rep-16-0031
|View full text |Cite
|
Sign up to set email alerts
|

The role of syncytins in human reproduction and reproductive organ cancers

Abstract: Human life begins with sperm and oocyte fusion. After fertilization, various fusion events occur during human embryogenesis and morphogenesis. For example, the fusion of trophoblastic cells constitutes a key process for normal placental development. Fusion in the placenta is facilitated by syncytin 1 and syncytin 2. These syncytins arose from retroviral sequences that entered the primate genome 25 million and more than 40 million years ago respectively. About 8% of the human genome consists of similar human en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 98 publications
1
35
0
Order By: Relevance
“…Moreover, problems during gestational diabetes are linked to aberrant expression of syncytin-2 and its receptor, MFSD2 [64]. The role of syncytins in the placenta is discussed in detail in a recent review [65]; here, we are concerned with the epigenetic regulation of syncytin expression.…”
Section: Examples Of Herv Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, problems during gestational diabetes are linked to aberrant expression of syncytin-2 and its receptor, MFSD2 [64]. The role of syncytins in the placenta is discussed in detail in a recent review [65]; here, we are concerned with the epigenetic regulation of syncytin expression.…”
Section: Examples Of Herv Regulationmentioning
confidence: 99%
“…High levels of syncytin-2 are detected in the testes, which is another tissue that displays global hypomethylation and this is thought to favour HERV expression [65]. Syncytin-1 is also thought to be involved in fertilisation, possibly contributing to the fusion of gametes.…”
Section: Examples Of Herv Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that syncytin-1 and estrogen stimulation induction is closely related, and which is in the cytotrophoblast fusion into the process of syncytium trophoblast key action [15]. It has been con rmed that the expression level of syncytin-1 is related to clinical manifestations in organ cancer patients [16], acute myeloid leukemia [17], breast cancer [18], endometrial carcinomas [19], ovarian cancer and colorectal cancer [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Chief among them are syncytin-1 and syncytin-2, which are considered hallmarks of terminal differentiation of placental trophoblast linage. 18 The synthesis and expression of syncytins depends on the cAMP/protein kinase A pathway as demonstrated through experiments that involve pharmacologic stimulation of cytotrophoblast-like (BeWo) cells with the adenylate cyclase activator and intracellular cAMP-elevating agent forskolin. 16,19 From the above experimental data it is tempting to speculate that aberrant expression and activation of a 2 ARs could disrupt placental development, leading to pathologic processes.…”
mentioning
confidence: 99%